Desenvolvimento e caracterização de sistemas líquido-cristalinos para aplicação tópica de metotrexato: estudos de liberação, retenção e permeação in vitro - Von Zuben, Eliete de Souza [UNESP] (2012)
Widely used in the treatment of some types of cancer, the methotrexate (MTX) is a chemotherapeutic, structurally analog of the folic acid, although its effectiveness, presents a series of adverse effect, being the most serious hepatotoxicity. Currently, the liquid crystal lamellar phase is being used of devices for modified release of drug demonstrated to be advantageous in the release topic of some substances, given to the characteristics of interaction with the stratum corneun and other layers of the skin, avoiding systemic adverse effects. The aims of this research had been to develop and to characterize liquid crystalline nanostructure systems of lamellar phase, increased of MTX of the physical point of view, also carry through the structural analysis of the formulations through by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS) and rheological properties. Perform stability studies of the chosen formulations, validate the analytical method of quantification of MTX for High Performance Liquid Chromatography (HPLC) and carry through release assay, cutaneous permeation and skin retention in vitro for the chosen formulations. The formulations prepared by the mixture of polyether functional siloxane as surfactant, with silicone polyether copolymer as oily phase and phosphate buffer 0,01M pH 7,4 as aqueous phase demonstrating lamellar liquid-crystalline phases, confirmed by assays of PLM and SAXS. The stability studies showed that formulations A, B and C remained stable throughout the period of the study. The study of the rheological behavior of the formulations presented as not Newtonian pseudoplastic fluid and thixotropic ...